Sistemas pecuários patronais e não patronais: uma perspectiva comparada do produto e aceitação pelo mercado consumidor - Conceição, Viviane Garcia Dias da (2022)
The complexity of the rural environment is due, in large part, to the heterogeneity of production systems and, within these systems, it is possible to classify them by the use or not of paid labor within the properties. Specifically, non-employer livestock systems still maintain the characteristic of being more traditional in their production in order to ensure the autonomy of the family group, which can often lead to worse production indicators. However, despite the limitations that this category finds, it has great social, economic and environmental relevance, making it important to understand the dynamics of these environments and their possible reflection on the scope of the refrigeration industry and on the consumer market. In this sense, this work aims to analyze and compare characteristics of carcasses from non-employer and employer systems, as well as identify the perception of consumers regarding the non-employer system and its product. The research was carried out in two stages: database analysis and a questionnaire. For data analysis, slaughter data from 2010 to 2013 were collected in a meatpacking industry, located in the center of the state of Rio Grande do Sul. 437,332 from cattle ranchers, in which cold carcass weight, dentition, finishing degree and quality program were evaluated. The differentiation between the livestock models was made from the existence or not of employees, declared by rural producers in the sale of their animals to the slaughterhouse. Data were submitted to analysis of variance, evaluating the effect between production systems and their interactions with sex, months and years, using the number of animals in each batch as a covariate, which was the experimental unit. To analyze the consumers' perception, a questionnaire was applied, with objective questions and free association of words, totaling 550 respondents. Data were collected between April and June 2021. The words of greatest impact remembered by respondents were subdivided into dimensions and categories, an exploratory technique of multivariate statistics was also used to distinguish the perception of consumers, and the same was performed through Principal Component Analysis (PCA) based on a variance- covariance matrix. Animals from non-employer livestock systems had, on average, lower cold carcass weight, greater maturity, lower degree of finishing and lower participation in quality programs, differing (P<0.05) from animals from employer livestock. Females did not differ (P>0.05) regarding dentition and degree of finishing between production systems. Over the months, regardless of gender, they did not differ (P>0.05) regarding the degree of finishing, except in February and December when animals from the employer's livestock were better finished. In the free association of words, it was identified that the dimensions family aspects, production chain, hedonic attitudes and feelings, food/products and sustainability characteristics were the most cited when consumers thought of non-employer livestock systems. Consumers believe that there is no difference between animals produced in different systems. Some consumers associate production in non-employer systems with environmentally correct production processes. However, even though there is a difference in favor of carcasses from employer livestock systems, the interviewed consumers demonstrate that there is room for differentiation of products from non-employer livestock systems, willing to pay higher amounts for certified products of this social category.